OTA-based electronically variable floating inductance simulator - Longsomboon, Kittisak; Petchmaneelumka, Wandee; Cheypoca, Thepjit; Riewruja, Vanchai (My University, 2011)
A circuit technique to implement a floating inductance simulator using operational transconductance amplifiers (OTAs) is introduced in this paper. The realization method based on the commercially available OTA, one resistor and one capacitor provides the advantage of an electronic adjusting capability. The resulting inductance can be electronically varied by tuning the external bias current of OTA. The obtained simulator is also applied in system response compensation. Experimental results verifying the circuit performances are included. © 2011 ICROS.
Keywords: electronic tuning means; inductance simulator; OTA; phase-lead compensator